Colonial urbanism in the age of the Enlightenment : the Spanish bourbon reforms in the river plate - Murray, Claudia (Anthem studies in Latin American literature and culture., 2023)
This book tells the story of how the monarchy aimed at creating a new capital city in a remote and forgotten area of the empire and shows how the local Creole bourgeoisie rapidly assumed the role of urban developers and enhanced their economic status by investing in and controlling the Buenos Aires? property market. During the eighteenth century, the Bourbon monarchy set about making geopolitical changes in the colonies in order to encourage trade. Buenos Aires was designated as the new capital city of the Viceroyalty of the River Plate in 1776. However, the city had at the time very little urban infrastructure it did not even have a cathedral or appropriate government buildings to welcome high-ranked bureaucrats from Spain, such as the Viceroy. Streets were mainly unpaved, dusty and there were no parks or promenades like in other capitals, where the eighteenth-century society could parade in fine clothes and displayed their often newly acquired social status.